A qualitative study exploring the feasibility and acceptability of computerised adaptive testing to assess and monitor children and young people's mental health in primary care settings in the UK - Lan, William; Anderson, Joanna; Stochl, Jan; Jones, Peter B; Ford, Tamsin; Burn, Anne-Marie (BMJ mental health, 2025)
BACKGROUND: The increasing prevalence of mental health disorders among adolescents highlights the importance of early identification and intervention. Artemis-A is a web-based application of computerised adaptive testing (CAT), originally developed for secondary schools, to quickly and efficiently assess students' mental health. Due to its speed, reliability and accessibility, it may be a valuable tool for healthcare practitioners (HCPs) working with children and young people (CYP) in primary, community and potentially secondary care settings in the future. OBJECTIVE: To explore whether Artemis-A would be a useful, feasible and acceptable tool for HCPs working in primary and community care settings to identify CYP's mental health difficulties. METHODS: Semistructured interviews were conducted with 20 HCPs: 5 general practitioners, 5 Child and Adolescent Mental Health Services (CAMHS) staff, 5 school nurses and 5 community paediatricians. Data were analysed using the Framework approach. FINDINGS: HCPs reported that Artemis-A has the potential to enhance mental health assessment and aid overburdened services by providing a quick, patient-centred assessment and monitoring mechanism. Benefits of the app include facilitating earlier intervention and appropriate referrals. However, some concerns emerged about safety netting and the way Artemis-A presents its information. Responsibilities for ensuring care continuity also require careful clarification. CONCLUSIONS: With proper protocols and integration, Artemis-A could prove valuable in supporting HCPs to promptly detect mental health issues in CYP. Further research into optimal implementation is warranted. CLINICAL IMPLICATIONS: If paired with effective evidence-based interventions, the implementation of Artemis-A could help manage escalating demands in CAMHS.
Keywords: mladiství; mužské pohlaví; Spojené království; Adult; studie proveditelnosti; služby péče o duševní zdraví; dítě; Child; kvalitativní výzkum; Diagnosis, Computer-Assisted; primární zdravotní péče; Mental Disorders; Qualitative Research; ženské pohlaví; Humans; diagnóza počítačová; Mental Health Services; United Kingdom; duševní poruchy; Child & adolescent psychiatry; dospělí; Female; Adolescent; Primary Health Care; Feasibility Studies; lidé; Male